Acclimatization response to a short-term heat wave during summer in lactating Brown Swiss and Holstein Friesian cows - Maggiolino, Aristide; Forte, Lucrezia; Aloia, Alessandra; Bernabucci, Umberto; Trevisi, Erminio; Lecchi, Cristina; Ceciliani, Fabrizio; Dahl, Geoffrey E.; De Palo, Pasquale (Frontiers in Veterinary Science, 2025)
IntroductionDairy cows are highly susceptible to heat stress, raising concerns about animal welfare, production efficiency, and economic losses. Previous studies suggest that Holstein and Brown Swiss breeds exhibit different levels of thermal tolerance, but their short-term adaptive responses require further investigation.MethodsThis study aimed to evaluate breed-specific physiological and productive responses to a 4-day natural heat wave in 40 lactating cows (20 Holstein, 20 Brown Swiss) from the same commercial dairy farm, homogeneous for days in milk, body condition score, parity, and energy-corrected milk yield. Before the heat wave, cows experienced at least 48 h in thermoneutral conditions. Physiological parameters were recorded three times daily (4:00 AM, 3:00 PM, and 8:00 PM). Blood samples were collected before the heat wave (D1, 4:00 AM, thermoneutral conditions) and at the warmest moment of the fourth day (D4, 3:00 PM, heat stress conditions).Results and DiscussionThe heat wave negatively impacted physiological parameters in both breeds. Rectal temperature increased daily from 4:00 AM to 3:00 PM (p < 0.01), with Holstein cows showing consistently higher values than Brown Swiss (p < 0.01). Respiration rate reached its lowest point at 4:00 AM each day (p < 0.01) but remained elevated at 8:00 PM, despite decreasing THI, indicating accumulated heat load. While both breeds followed a similar trend, Holsteins exhibited a greater capacity for overnight recovery compared to Brown Swiss. Regarding productivity, Brown Swiss cows maintained stable milk yield (MY) from D1 to D4, whereas Holsteins showed a progressive MY decline throughout the heat wave (p < 0.01). Most blood parameters showed no significant breed differences (p > 0.05), but heat shock protein 70, a key regulator of thermal adaptation, exhibited an increasing trend in both breeds (p < 0.01), appearing earlier than other physiological indicators of heat stress.ConclusionThis study, conducted under identical conditions, highlights distinct breed-specific responses to short-term heat stress. The findings suggest that Brown Swiss cows may be more resilient to heat stress in terms of productivity, while Holsteins show better nighttime recovery. Further research should explore additional physiological and molecular markers to better characterize breed differences and improve heat stress mitigation strategies in dairy farming.